2019
DOI: 10.1021/acsami.9b03194
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine-Doped Graphene Quantum Dots with Enhanced Anti- and Pro-Oxidant Properties

Abstract: Production or elimination of highly reactive oxygen species is critical in antioxidant, photodynamic, therapeutic, and antibacterial applications. Recent studies have demonstrated that graphene quantum dots (GQDs) possess anti- and pro-oxidant properties simultaneously. However, their efficiency is low. Here, we report chlorine-doped GQDs (Cl-GQDs) with a tunable Cl doping amount and improved anti- and pro-oxidant activities. The scavenging performance and the free radical-produced efficiency of Cl-GQDs are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 49 publications
2
73
0
Order By: Relevance
“…DPPH free radical assay was performed to evaluate the antioxidant potential of FA-SGQDs using a previously reported method with minor modifications [31], as described in detail in the section 1 of Electronic Supplementary Material.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…DPPH free radical assay was performed to evaluate the antioxidant potential of FA-SGQDs using a previously reported method with minor modifications [31], as described in detail in the section 1 of Electronic Supplementary Material.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…The C 1s spectra of N-CDs, P-CDs, and S-CDs showed that the intensities of C=C, C=O, and OÀ C-O groups of u-CDs also reduced to some extent after the reaction with DPPH, similar to the previous study. [47]…”
Section: Phenolic Content and Antioxidant Activitymentioning
confidence: 99%
“…17 Recently, a series of carbogenic nanodots, such as graphene quantum dots (GQDs), nitrogen-doped carbon dots, selenium-doped carbon dots, chlorine-doped GQDs, and nitrogen/sulphur-co-doped carbon dots, have emerged as antioxidants for ROS elimination. [18][19][20][21][22][23][24][25] In particular, GQDs have shown efficient renal clearance properties and long body retention, providing them great kidney targeting ability. 26,27 Signicantly, the biological effects of GQDs functionalized with enriched oxygenated groups have been investigated exhaustively, and they exhibit high biocompatibility both in vitro and in vivo even at a high dose.…”
Section: Introductionmentioning
confidence: 99%